Impact of cis-zeatin and lovastatin on antioxidant systems and growth parameters in Zea mays seedlings under phytohormonal crosstalks - Yousaf, Muhammad Junaid; Hussain, Anwar; Hamayun, Muhammad; El-Sheikh, Mohamed A.; Elansary, Hosam O.; Kim, Ho-Youn (Taylor & Francis, 2024)
Phytohormones are essential regulators that control both plant growth and defense mechanisms, with cytokinins (CKs) playing a crucial role in regulating antioxidants. However, conflicting research results regarding their effect on antioxidants require further investigation. This study addresses the effects of cis-zeatin (cZ), a type of CK, and its inhibitor lovastatin (LT) on the antioxidant system of 29-day-old Zea mays plants. Seedlings were treated by aerial spraying with 5 M cZ, LT, or their combination (cZ-LT) five days after planting. The results showed that cZ significantly increased growth performance, antioxidant activity and photosynthesis efficiency. cZ treatment increased the accumulation of osmolytes (including total phenolics, total flavonoids, proline, and total soluble proteins), resulting in larger leaves, longer shoots, and increased biomass while reducing root length and biomass, respectively. In contrast, LT treatments resulted in reductions in leaf size, shoot length, and biomass, as well as impairment in photosynthesis rates. LT-treated seedlings showed reduced osmolyte accumulation but increased antioxidant enzymatic activity, which contributed to an increase in electrolyte leakage. Examination of phytohormonal crosstalk showed that cZ treatment increased endogenous GA4 and cZ levels while decreasing IAA levels, while LT had opposite effects. These results provide insights into the complex interplay of phytohormones in modulating both plant growth and antioxidant defense mechanisms.